Developments and Needs for Sustainable Agro-Logistics in Developing Countries - van der Vorst, Jack G.A.J. (World Bank, Washington, DC, 2014)
The Multi-Donor Trust Fund for Sustainable Logistics (MDTF-SL) aims at promoting innovative assistance projects that can break new grounds, test new ideas, and generate new knowledge for sustainable logistics that can be replicated in other countries and project. In November 2013 we were asked to write a position paper that analyses the state of affairs in Agro-Logistics. It aims to: (1) review and suggest a conceptual grounding for the MDTF-SL's activities; (2) outline the specific challenges developing countries face on Agro-Logistics; and (3) review existing attempts or interventions to meet the identified challenges. This position note starts with a definition for agro-logistics to have a mutual understanding of the concept. Section two presents emerging global trends and developments, which are then, translated to key logistics objectives in section three. Next, in section four, five international cases are presented that illustrate the needs and key bottlenecks in agro-logistics for developing countries. Section five presents an overview of potential interventions to improve logistics performances, resulting in recommendations (section six).